2020
DOI: 10.1101/2020.07.08.194084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for helicase-polymerase coupling in the SARS-CoV-2 replication-transcription complex

Abstract: SUMMARYSARS-CoV-2 is the causative agent of the 2019-2020 pandemic. The SARS-CoV-2 genome is replicated-transcribed by the RNA-dependent RNA polymerase holoenzyme (subunits nsp7/nsp82/nsp12) along with a cast of accessory factors. One of these factors is the nsp13 helicase. Both the holo-RdRp and nsp13 are essential for viral replication and are targets for treating the disease COVID-19. Here we present cryo-electron microscopic structures of the SARS-CoV-2 holo-RdRp with an RN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 97 publications
4
46
0
Order By: Relevance
“…1d). These shifts indicate stabilization via ligand binding, and are consistent with recent structural data showing ADP:AlF3 binding within the nsp13 active site 5 (Fig. 1d).…”
Section: Biochemical Characterization Of Sars-cov-2 Nsp13supporting
confidence: 91%
See 4 more Smart Citations
“…1d). These shifts indicate stabilization via ligand binding, and are consistent with recent structural data showing ADP:AlF3 binding within the nsp13 active site 5 (Fig. 1d).…”
Section: Biochemical Characterization Of Sars-cov-2 Nsp13supporting
confidence: 91%
“…The efficiency of nsp13 unwindase activity is low compared to other helicases, but may be enhanced by either cooperativity or by interaction with the viral RdRp [8][9][10] . Consistently, recent structural data has shown that SARS-CoV-2 nsp13 can form a complex with RdRP 5 . Nonetheless, the potential mechanisms underlying nsp13 activation have not been explored.…”
supporting
confidence: 81%
See 3 more Smart Citations